Modeling and Simulation of the Itm Model for Point to Point Prediction on Digital Television Extensible to Other Technologies - Kaschel-Carcamo, H; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2018)
This article addresses the main characteristics and structure of the most widely used propagation model to predict analogue and digital radio coverage in a point to point mode. The ITM model, ITS-67 (Institute of Telecommunications Sciences) V1.2.2. a.k.a ITM Longley Rice (Irregular Terrain Model), is deterministic and based on NBS (National Bureau of Standards) TN101 Vol.12. In this article, the ITM evolution in its different versions is analyzed, the four zones of the ITM are described as well as the signal attenuation level displayed in a continuous function between the Transmitter and the Receiver. The ITM V1.2.2 algorithms coefficients and profile are described and analyzed, including the calculation of the continuous function of reference attenuation, the terrain irregularity parameter Δ h and variabilities. Then, three existing radio links part of a TVD radial previously measured, are simulated with the last version of Radio Mobile program and the results compared with the measurements. © 2018 IEEE.